Optimisation of piezoelectric and dielectric properties of Bi4Ti2.95W0.05O12 ceramics by Ce4+ doping - Chen Tao; Liu Tiantian; Chen Yang; Qi Zhang (Processing and Application of Ceramics)
High-temperature lead-free Bi4-xCexTi2.95W0.05O12 (where x = 0, 0.02, 0.04, 0.06) piezoelectric ceramics were prepared by conventional solid-state method and sintering at 1080°C. This study investigated the effects of modulating the degree of ceramic lattice distortion by varying the amount of Ce4+ doping on the microscopic morphology as well as the piezoelectric and dielectric properties. The results indicated that an appropriate level of Ce4+ doping resulted in a suitable degree of lattice distortion within the piezoelectric ceramics, thereby enhancing both the piezoelectric and dielectric properties while reducing dielectric losses. Notably, when the doping level reached x = 0.04, the sample exhibited its optimal performance, specifically with a d33 of 25 Pc/N, TC of 618°C, tan δ of 0.09 and Qm of 3364. These findings strongly suggest that this material has significant potential for applications in high-level sensing domain.